Çevrimiçi öğrenme topluluklarının öğretmenlerin mesleki gelişimine etkisine yönelik öğretmen görüşleri - Sarıdaş, Gürkan (My University, 2017)
Araştırma bulgularına dayanarak informal bir şekilde öğretmenler tarafından oluşturulan çevrimiçi öğrenme topluluklarının olumlu yönde mesleki gelişime katkısı olduğu ortaya çıkmış ve öğretmenlerin kendi bilgi, beceri, deneyim, tutum gibi davranışlarını geliştirmede bu topluluklardan faydalandıkları gözlenmiştir. Bu fayda sağlama durumu ise en çok hızla değişen öğretim yöntem ve teknikleri ve öğrenci merkezli uygulamalarda gözlenmiştir.

Professional development has been an important process in terms of teachers being learning individuals and renewing themselves. The purpose of the professional development process is to improve the knowledge, skills, values and attitudes of the teachers. The process is being divided into two categories; school-based professional development and non-school professional development. As well as these non-school professional development studies have been conducted by the trainings held by various institutions and organizations; the teachers have tried to contribute to the process with their own self - created communities, as well. These informal learning communities have been created in a variety of contexts. With the help of developments and changes in the field of technology, these communities created by the teachers have been moved to the web environment and ‘online learning communities’ have been created. Cooperative learning has emerged as a result of the interaction between the community - building teachers and the community members.The purpose of this study, is examining the effects of the self - created online learning communities, to the professional development of the teachers who created them. In accordance with this purpose; the contribution made to the professional development, the challenges and facilitating effects, the difficulties in supplying the needs of teachers from the environment or schools, the teachers’ online mobilities in these communities, the private sphere and the general professional qualifications which influence the teachers’ perspectives, the point of being strong, weak and sides which need to be improved, the opinions about the teachers who do not participate in online learning communities were investigated and determined. For this purpose, 287 teachers who had been working in Denizli province and who had mobility in online environment were reached by the usage of snowball sampling method; semi – structured interview technique was applied and interview results were analyzed by using descriptive analysis approach. In the scope of the research; it was found that, teachers mostly used the Facebook groups; a large majority were active in these groups all along the day and they tended to get immediate access to the content shared within the community which they attend, to examine and contribute to it. Teachers benefited from most of the teaching methods and techniques related to their specific areas; and in general vocational sense, they used it in the point of following current issues. Interviewed teachers stated that these communities contributed to their professional development and that this contribution helped to transfer various knowledge and skills to the educational environment. The accuracy of the information disseminated in the communities, was at the forefront of the difficulties faced by teachers; on the other hand, the easy and rapid access to the information was the greatest facilitating effect of these communities. Interviewed teachers got involved to these communities to supply their needs to the new information and they expect for other teachers to participate, as well. Compared to the other professional development communities, the reasons for these teachers to choose online communities are financial difficulties. They expressed the desire to make communities more innovative while they have identified the superior side of online environments as rapid accession. Accessibility in these communities was among the strengths, while reliability was among the weaknesses. While they thought for the teachers who were not in these communities missed a lot, they made suggestions to them for participating. Compared with the traditional learning communities, it has been found that online learning communities were faster at reaching information and practice. On the basis of research findings, it has been found that online learning communities created by teachers in informal forms have been contributing positively to the professional development and it has been observed that teachers benefit from these communities on the point of developing their own knowledge, skills, experience and attitudes. This situation has been observed especially in student-centered practices and in the teaching methods and techniques, which have been rapidly changing.
Keywords: çevrimiçi öğrenme; çevrimiçi öğrenme ortamları Vocational development; çevrimiçi öğrenme toplulukları; Eğitim; Mesleki gelişim; online learning; online learning communities; online learning environments; Teknoloji; Türkiye; Yönetim